2011
DOI: 10.1007/s00394-010-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

Relation of body mass index to blood folate and total homocysteine concentrations in Japanese adults

Abstract: 2 AbstractPurpose Plasma folate concentrations are suggested to be negatively associated with body-mass index (BMI, kg/m 2 ), although these findings are controversial. Our objective was to evaluate the association of BMI to blood folate and total homocysteine (tHcy) concentrations. MethodsWe measured plasma and erythrocyte folate and plasma tHcy concentrations in 434 healthy adults (343 women and 91 men; mean age of 63.8 ± 10.7 [SD, range 23-88] years old), who participated in a 2007 population-based survey i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
3
15
1
Order By: Relevance
“…Since only 4 students was classified as BMI ≥ 25 and had low serum folate concentrations, further studies are needed to confirm the association of BMI and serum folate concentrations. There were no significant associations between BMI and RBC folate concentrations in both male and female students and these results are consistent with previous studies [15,31]. Our data shows that the students who practiced physical activity for 30 min/day three times or more per week had higher folate intake and blood folate concentrations even after controlling for other health-related behaviors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since only 4 students was classified as BMI ≥ 25 and had low serum folate concentrations, further studies are needed to confirm the association of BMI and serum folate concentrations. There were no significant associations between BMI and RBC folate concentrations in both male and female students and these results are consistent with previous studies [15,31]. Our data shows that the students who practiced physical activity for 30 min/day three times or more per week had higher folate intake and blood folate concentrations even after controlling for other health-related behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Higher BMI has been shown to be associated with lower serum folate concentrations in male and female adults [31], as well as in child-bearing age women [15]. Serum folate concentration in female students whose BMI is higher than 25 was significantly lower compared to those less than 25, but no association was found after controlling for other health-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of body weight on bone mass may be attributable to a number of factors: increased mechanical load which has an anabolic effect on bone [4]; conversion of steroid precursors to estrogen in peripheral adipose tissue [5] or through the secretion of bone active hormones from β-cells in the pancreas and adipocytes themselves [6]. Homocysteine (Hcy), vitamin B12, vitamin D and folate are biomarkers for a number of pathologies including cardiovascular disease and diabetes and a strong correlation between these biomarkers with BMI has been reported [7][10]. Elevated levels of Hcy and low levels of vitamin D are strong and independent risk factors for osteoporotic fracture risk [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, homocysteine was not associated with BMI among normal weight, overweight, or obese subjects, nor in the whole population after adjusting for cardiac medication use, or when looking exclusively at those without diabetes. Conflicting results between BMI and circulating homocysteine levels have been reported, and a recent study of men and women in Western Japan also showed no association between BMI and plasma homocysteine 31. In contrast, CRP and fibrinogen were positively associated with BMI in the overall population and among obese subjects, with strong positive associations additionally noted among overweight and normal weight subjects for CRP.…”
Section: Discussionmentioning
confidence: 85%